Mathematical modeling of an amperometric glucose sensor: the effect of membrane permeability and selectivity on performance - Abd. Aziz, Azila (Penerbit UTM Press, 2009)
Interference from electro-active chemicals such as ascorbic acid, uric acid and acetaminophen can be a problem for peroxide based glucose biosensors. Most works focused on the employment of a perm-selective membrane sandwiched between the electrode and the active component of the sensor to overcome this problem. In this work, a mathematical model has been developed to study the effect of membrane permeability and selectivity on peroxide based glucose biosensor performance. Digital simulation was carried out using the finite difference method. As expected, membrane selectivity to peroxide played a major role in interference reduction. However, interestingly, the model also suggested that the manipulation of the transport properties of the protective outer layer would also result in acceptable interference reduction.